Group Revision is Better Than Self-Revision in Case of Mathermatics - S M Nazmuz Sakib (Noumerico: Journal of Technology in Mathematics Education, 2025)
One of the most common dilemmas faced by students studying mathematics is whether to opt for group revision or self-revision. Given the increasing perception of mathematics as a challenging and less engaging subject, selecting the most effective revision strategy is crucial. This study systematically reviews existing literature to analyze the comparative benefits and drawbacks of group and self-revision in mathematics education. The research employs a systematic literature review methodology, synthesizing findings from academic studies that explore the cognitive, motivational, and pedagogical aspects of both revision methods. The analysis reveals that while individual preferences and learning styles play a role, group revision generally yields better academic performance, increased motivation, and enhanced conceptual understanding compared to self-revision. The findings have implications for students, educators, and administrators in optimizing pedagogical strategies to enhance mathematics learning outcomes